Diagnostic angiography skill acquisition with a secondary curve catheter: phase 2 of a curriculum-based endovascular simulation program. (3rd September 2014) - Spiotta, Alejandro M; Kellogg, Ryan T; Vargas, Jan; Chaudry, M Imran; Turk, Aquilla S; Turner, Raymond D
Abstract : Background: We have previously reported the efficacy of a simulator-based training paradigm for residents in neurosurgery with little or no prior experience in diagnostic cerebral angiography with straightfoward arch anatomy. This study investigates the utility of a simulation-based training curriculum for the acquisition of skills employing a secondary curve catheter to navigate more complex arch anatomy. Methods: Residents at the Medical University of South Carolina (MUSC) with moderate exposure to diagnostic angiography enrolled into a standardized Institutional Review Board-approved training protocol using SimSuite Compass and Simbionix simulators. The task involved (in order) forming the Simmons catheter in the left subclavian artery and then selecting the brachiocephalic, left common carotid and left vertebral arteries. Results: All participants improved their total time to complete the task over the course from the first to last trial. Each milestone within the overall task also demonstrated an improvement across trials for each participant. Following the hands-on experience, participants' rating of their knowledge of arch anatomy and vessel selection technique improved to that between competence and high competence (values of 3.3±0.49 (p<0.005) and 3.1±0.38 (p<0.01), respectively). Comfort with use of the Simmons catheter improved to a value of 2.9±0.38 (p<0.001), between an experienced learner and competence. Participants rated the usefulness of the training environment as very high (4.1±0.90 out of maximum 5). Conclusions: Residents became more proficient at vessel selection in a type II and bovine arch over a relatively compressed time period, with both objective and subjective data demonstrating acquisition of skill sets and increased confidence.